2016
DOI: 10.1161/circresaha.115.306566
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Coronary Artery Disease

Abstract: Genetic factors contribute importantly to the risk of coronary artery disease (CAD), and in the past decade, there has been major progress in this area. The tools applied include genome-wide association studies encompassing >200 000 individuals complemented by bioinformatic approaches, including 1000 Genomes imputation, expression quantitative trait locus analyses, and interrogation of Encyclopedia of DNA Elements, Roadmap, and other data sets. close to 60 common SNPs (minor allele frequency>0.05) associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
223
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(234 citation statements)
references
References 147 publications
(155 reference statements)
2
223
0
9
Order By: Relevance
“…ANK, ankyrin repeats; EGF, epidermal growth factor; HD, heterodimerization domain; LNR, Lin-Notch repeats; PEST, proline (P), glutamic acid (E), serine (S) and threonine (T) degradation domain; RAM, Rbp-associated molecule domain; SP, signal peptide; TM, transmembrane domain. diseases, ranging from autism spectrum disorders and schizophrenia to heart disease (McPherson and Tybjaerg-Hansen, 2016;Mitchell, 2011). Recently, the Exome Aggregation Consortium (EXAC) has pooled data and resources to generate the largest database of human sequencing data, including 60,706 individuals (Lek et al, 2016).…”
Section: Insights From 'Big Data' Analysesmentioning
confidence: 99%
“…ANK, ankyrin repeats; EGF, epidermal growth factor; HD, heterodimerization domain; LNR, Lin-Notch repeats; PEST, proline (P), glutamic acid (E), serine (S) and threonine (T) degradation domain; RAM, Rbp-associated molecule domain; SP, signal peptide; TM, transmembrane domain. diseases, ranging from autism spectrum disorders and schizophrenia to heart disease (McPherson and Tybjaerg-Hansen, 2016;Mitchell, 2011). Recently, the Exome Aggregation Consortium (EXAC) has pooled data and resources to generate the largest database of human sequencing data, including 60,706 individuals (Lek et al, 2016).…”
Section: Insights From 'Big Data' Analysesmentioning
confidence: 99%
“…Furthermore, clustering of CAD in Asian Indian families indicates genetic risk factor/susceptibility (48). Coronary Artery Disease Genome-wide Replication and Meta-analysis (CARDIOGRAM) study and other genome-wide association studies (GWAS) have found 109 loci associated with CAD and can explain 28% of the heritability (49,50). One likely explanation for the low heritability can be the polygenic nature of CAD.…”
Section: Non-modifiable Factorsmentioning
confidence: 99%
“…Si bien hubo hallazgos interesantes respecto de este SNP, como la existencia de tres pacientes homocigotas GG con calcificaciones en dos territorios diferentes (coronaria y aorta torácica), su vinculación con la regulación de los niveles Lp(a) recién se está iniciando, ya que fue descubierto en el corriente año (2016). (8,9) Acorde a lo esperado, dado que el bajo número de repeticiones se asocia con niveles altos de Lp(a), se encontró que en el 72% de los pacientes estudiados el número de repeticiones del Kringle IV-2 es menor que el que presentan pacientes con niveles de Lp(a) normales.…”
Section: Discussionunclassified
“…(3-5, 7) Asimismo, a principios del año 2016, mediante estudios de GWAS (Genome Wide Association Study), se ha descripto un nuevo SNP en el gen SLC22A3 (rs2048327) que estaría vinculado a enfermedad vascular coronaria influyendo los niveles de Lp(a). (8,9) En base a los nuevos conocimientos en cuanto a la base genética de la determinación de los niveles de Lp(a), utilizando modernos métodos de biología molecular, es posible estudiar tanto el número de repeticiones del KIV en el gen LPA como los SNP relacionados con mayor riesgo. (5) La tomografía computarizada cardíaca y en especial el puntaje de calcio coronario han demostrado ser los predictores más fuertes de eventos coronarios, posibilitando la reclasificación del riesgo cardiovascular.…”
Section: Introductionunclassified